Integrin αvβ6 critically regulates hepatic progenitor cell function and promotes ductular reaction, fibrosis, and tumorigenesis - Peng, Zhen‐Wei; Ikenaga, Naoki; Liu, Susan B.; Sverdlov, Deanna Y.; Vaid, Kahini A.; Dixit, Richa; Weinreb, Paul H.; Violette, Shelia; Sheppard, Dean; Schuppan, Detlef; Popov, Yury (Hepatology (Baltimore, Md.), 2016)
Integrin αvβ6 is rapidly up‐regulated on cells of epithelial lineage during tissue injury, where one of its primary functions is activation of latent transforming growth factor beta 1 (TGFβ1). In human liver cirrhosis, αvβ6 is overexpressed by cells comprising the ductular reaction, and its inhibition suppresses experimental biliary fibrosis in rodents. Here, we show that αvβ6 is expressed on the actively proliferating subset of hepatic progenitor cells and is required for their progenitor function in vivo and in vitro through integrin αvβ6‐dependent TGFβ1 activation. Freshly isolated αvβ6+ liver cells demonstrate clonogenic potential and differentiate into cholangiocytes and functional hepatocytes in vitro, whereas colony formation by epithelial cell adhesion molecule‐positive progenitor cells is blocked by αvβ6‐neutralizing antibody and in integrin beta 6‐deficient cells. Inhibition of progenitors by anti‐αvβ6 antibody is recapitulated by TGFβ1 neutralization and rescued by addition of bioactive TGFβ1. Genetic disruption or selective targeting of αvβ6 with 3G9 antibody potently inhibits progenitor cell responses in mouse models of chronic biliary injury and protects from liver fibrosis and tumorigenesis, two conditions clinically associated with exacerbated ductular reaction. Conclusion: These results suggest that αvβ6 is a promising target for chronic fibrotic liver diseases and associated cancers. (Hepatology 2016;63:217–232)